Comparing three methods of assessment of psoas area as a proxy for sarcopenia in predicting short-term outcomes in trauma patients 55 years and older - Meader, Anna. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Kent.; Committee: Mihaela Stefan, David Clark, Christine Lary, and Paul Han.; Keyword: Health sciences.